2019
DOI: 10.3389/fphys.2019.01167
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Drosophila and Its Context

Abstract: A prominent idea emerging from the study of sleep is that this key behavioural state is regulated in a complex fashion by ecologically and physiologically relevant environmental factors. This concept implies that sleep, as a behaviour, is plastic and can be regulated by external agents and changes in internal state. Drosophila melanogaster constitutes a resourceful model system to study behaviour. In the year 2000, the utility of the fly to study sleep was realised, and has since extensively contributed to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 185 publications
(320 reference statements)
1
50
0
Order By: Relevance
“…Current models of sleep regulation rely on two main processes, the circadian clock and the sleep homeostat and don't completely account for multiple external and internal factors that influence wakefulness 113 . The ability to sleep, however, is influenced by motivational or cognitive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Current models of sleep regulation rely on two main processes, the circadian clock and the sleep homeostat and don't completely account for multiple external and internal factors that influence wakefulness 113 . The ability to sleep, however, is influenced by motivational or cognitive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…If upd2 mutants are failing to process a feeding-related signal, then neural evidence of this “chronically starved” state might be evident in brain activity. Several neurons in the Drosophila brain reflect nutritional effects, including lateral horn leucokinin (LHLK) neurons and neuropeptide F (Npf) neurons (for a review, see [ 21 , 62 ]). Interestingly, certain neurons in the ellipsoid body (EB) in the central brain (which is involved in sleep as well as visual behaviors [ 44 , 63 ]) appear to be responsive to starvation cues: a previous study found that acute starvation increased the activity levels of R4 neurons in the EB [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of diet on sleep are complex and it is likely that the effects diet differs depending on genetic background, availability of nutrients during development and age . Previous work has shown that flies fed a diet of sugar alone sleep more than starved flies, suggesting that sugar promotes sleep .…”
Section: Discussionmentioning
confidence: 99%